Femtosecond laser–assisted cataract surgery: First clinical results with special regard to central corneal thickness, endothelial cell count, and aqueous flare levels. Issue 8 (August 2016) - Mariacher, Siegfried; Ebner, Martina; Seuthe, Anna‐Maria; Januschowski, Kai; Ivanescu, Ciprian; Opitz, Natalia; Szurman, Peter; Boden, Karl Thomas
Abstract : Purpose : To evaluate clinical data and outcomes after femtosecond laser–assisted cataract surgery with the recently introduced low‐energy Femto LDV Z8 laser during a 3‐month follow‐up. Setting : Knappschaft Eye Clinic Sulzbach, Knappschaft Hospital Saar GmbH, Sulzbach, Germany. Design : Consecutive case series. Methods : Femtosecond laser‐assisted cataract surgery was performed using the low‐energy femtosecond laser. Clinical data including objective refraction, corrected distance visual acuity, central corneal thickness (CCT), endothelial cell count (ECC), and aqueous flare were evaluated 1 day, 1 week, 4 weeks, and 3 months postoperatively. Results : The median CCT and aqueous flare were statistically significantly elevated during the first day and 4 weeks after surgery, respectively ( P < .001). There were no significant differences between CCT preoperatively and 1 week postoperatively ( P = .079) and aqueous flare preoperatively and 3 months postoperatively ( P = .082). No statistically significant difference was found in the median ECC and spherical equivalent refraction between preoperatively and postoperatively ( P > .05). Conclusion : Visual outcomes and investigated parameters reflecting corneal integrity indicated safe and atraumatic surgery using a new low‐energy femtosecond laser for laser‐assisted cataract surgery (including capsulotomy and lens fragmentation). Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.